Investigating EFL Students' Writing Skills Through Artificial Intelligence: Wordtune Application as a Tool - Mahmud, Fawaz Al (Journal of language teaching and research, 2023)
Artificial intelligence (AI) powered writing technologies such as Wordtune and Grammarly are increasingly penetrating the L2 writing domain. Despite the growing significance of such digital tools, few studies have explored how AI-driven applications impact Saudi English as a Foreign Language (EFL) writing. The current study aimed to fill this gap by investigating whether and to what extent Wordtune facilitates Saudi students' writing. The participants were divided into two male and two female groups using a mixed-method design. For both male and female samples, one group was identified as the control group, whereas the other one was identified as the experimental group. Quantitative data were collected using pretests and post-tests and analyzed using SPSS. Qualitative data were derived from students' writing samples and assessed by two human raters. The results showed that using Wordtune, students in the experimental group surpassed those in the control group. Quantitative findings demonstrated that using Wordtune, the experimental group upgraded their writing and outperformed the control group in the final writing exam. Qualitative findings indicate that using Wordtune, the experimental group made modest writing gains at the lexical and syntactic levels. While lexical gains included more concrete nouns, vivid adjectives, and precise verbs, sentence-structure gains included the increasing presence of complex phrases and complex and compound sentences. Finally, the impact of Wordtune on writing quality was the same for both male and female participants.